Money Politics and Dynasty Politics (Study of Critical Analysis of Threats to Indonesian Democracy) (JED (Jurnal Etika Demokrasi), 2024)
This article aims to understand and analyze the threats to Indonesian democracy that arise from monetary policy practices and dynastic policies as a means of competing for the government's strategic position. The basic concept of democracy by the people, for the people and from the people is only used as a political symbol to deceive the people. This study uses a qualitative research method with a meta-synthesis method to map research results from various literatures by exploring several literatures related to monetary policy and dynastic policy. The results of the research are, 1). Money politics is carried out by prospective politicians who give money to the people so that they get the people's vote in the sense that unscrupulous politicians buy democracy and when that happens, the people who enter the government are the people. who have lots of money. 2). At the same time, dynastic politics is a source of capital for politicians who have families in government to gain prestige in society. Thus, monetary policy and dynastic politics threaten democracy and the future of the Indonesian nation. The first problem in selecting a public official is whether the politician has a lot of money and prestige, in this case a family working in the government. The data is then analyzed to see the problems in Indonesian democracy so that those who are elected as political parties are qualified candidates and not because of the many politics or political dynasties.